PROFITABILITAS, LIKUIDITAS, RASIO PAJAK DAN STRUKTUR MODAL: STUDI HUBUNGAN KAUSALITAS PADA PERUSAHAAN-PERUSAHAAN SEB SEKTOR PERDAGANGAN BESAR BARANG PRODUKSI YANG LISTING DI BURSA EFEK INDONESIA PERIODE 2010-2014 - Akhmadi Akhmadi; Abdul Rosyid; Fitri Handayani (Jurnal Riset Akuntansi Terpadu, 2018)
The purpose of this study is to analyze and interpret the influence of profitability, liquidity and tax ratios on capital structure in the large trade sector that produces goods listed on the Indonesia Stock Exchange in 2010-2014. This type of research is an associative (causal) study. The population and sample used in this study were the Wholesale Goods Production Companies listed on the Stock Exchange for the 2010-2014 period as many as seven companies using purposive sampling. The data used is secondary data. Data analysis using multiple linear regression analysis. This study has empirical evidence that profitability in the capital structure has no significant positive influence. Liquidity in the capital structure has significant negative effect on the capital structure, whereas, tax ratio has a significant positive effect. Positive effect on the capital structure while, the tax ratio are significant positive effect.